Insights into Various Aspects of Oral Health - Francis Manakil, Jane (IntechOpen, 2017)
Chronic inflammation such as seen in periodontitis and its bidirectional influence on the systemic health has been of increased interest for a decade. In this text book, we have explored the biological and genetic pathways by which periodontal diseases may influence these disease processes and vice versa. Occlusal rehabilitation using the MEAW technique for the effective treatment of class II deep bite malocclusion and the timely management of cleft lip and palate to benefit the holistic welfare of the patient are presented here. The book addresses the development of bioinspired functionally graded dental restorative materials and also a simulation method that can improve clinical durability and enhance the functional capability of the dentition and indirect prostheses. In conclusion, various pathways for the promotion of oral health with evidence-based concepts are considered.